El culto de Afrodita armada en Amiclas (Esparta) y la fundación de Tarento - Valdés Guía, Miriam (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The existence and protagonism of a cult of armed Aphrodite in Sparta is especially relevant in the Archaism, besides other places, in Amyklai. The “oriental” features of the Goddess are perfectly integrated in their personality and, over all, the role as an armed Goddess must be understood in the context of the social relations and specifically of the relationships between men and women in these moments of polis formation, linked also with the formation and delimitation (and also ideological definition) of the citizenship; some sectors of the population are excluded of the citizenship, as the women or the Partheniai who leave to Tarent, in one version of the tradition, from Amyklai.